Challenges in Teaching Materials for Mathematics Capita Selecta Course: Insights from Prospective Secondary School Teachers - Wulandari, Suci; Mulyati, Asrina; Rahmalina, Widdya; Yunita, Andini Putri; Gusteti, Meria Ultra; Hayati, Rahmatul; Azmi, Khairul; Sukandar, Warlan (Prima: Jurnal Pendidikan Matematika, 2025)
The lack of learning resources that facilitate students in the Secondary School Mathematics Capita Selecta course served as the background for this study. This research aimed to investigate the challenges faced by prospective mathematics teachers in the Secondary School Mathematics Capita Selecta course at Universitas Adzkia. Using a descriptive-qualitative approach, this study involved 18 students and course instructors as participants. Data were collected through surveys and structured interviews, then analyzed to identify key themes related to learning difficulties. The results showed that students experienced difficulties in understanding abstract mathematical concepts, connecting theory with practical applications, and utilizing available learning resources. This condition indicates the need to develop systematic, varied, and interactive learning materials to improve student comprehension and motivation. This study also revealed that the integration of technology in learning can help students understand complex topics and create a more engaging learning environment. Therefore, the development of well-organized and technology-integrated learning resources is crucial to improve the effectiveness of the course and help students overcome learning obstacles. Based on these findings, it was concluded that the development of innovative and technology-integrated learning resources plays an important role in improving the quality of learning in the Secondary School Mathematics Capita Selecta course. Further research is recommended to explore more advanced technological interventions and collaborative learning techniques to enhance instructional delivery and student learning outcomes.